A third-person perspective on co-speech action gestures in Parkinson's disease. (May 2016) - Humphries, Stacey; Holler, Judith; Crawford, Trevor J.; Herrera, Elena; Poliakoff, Ellen
Abstract: A combination of impaired motor and cognitive function in Parkinson's disease (PD) can impact on language and communication, with patients exhibiting a particular difficulty processing action verbs. Co-speech gestures embody a link between action and language and contribute significantly to communication in healthy people. Here, we investigated how co-speech gestures depicting actions are affected in PD, in particular with respect to the visual perspective—or the viewpoint – they depict. Gestures are closely related to mental imagery and motor simulations, but people with PD may be impaired in the way they simulate actions from a first-person perspective and may compensate for this by relying more on third-person visual features. We analysed the action-depicting gestures produced by mild-moderate PD patients and age-matched controls on an action description task and examined the relationship between gesture viewpoint, action naming, and performance on an action observation task (weight judgement). Healthy controls produced the majority of their action gestures from a first-person perspective, whereas PD patients produced a greater proportion of gestures produced from a third-person perspective. We propose that this reflects a compensatory reliance on third-person visual features in the simulation of actions in PD. Performance was also impaired in action naming and weight judgement, although this was unrelated to gesture viewpoint. Our findings provide a more comprehensive understanding of how action-language impairments in PD impact on action communication, on the cognitive underpinnings of this impairment, as well as elucidating the role of action simulation in gesture production.